HPLC-UV Determination of Catechins and Gallic Acid in Aerial Parts of Astragalus glycyphyllos L. - Roman, Lysiuk; Solomiia, Kozachok (Dhaka University Journal of Pharmaceutical Sciences, 2019)
The aerial part of Astragalus glycyphyllos L. (Astragali glycyphylli herba), a promising nephroprotective agent in folk medicine, has been investigated by HPLC-UV for occurrence of catechins, which are known in individual state as renoprotective substances and gallic acid. The following six compounds were detected and quantitatively determined in the analyzed plant material: (-)-gallocatechin, (-)-epigallocatechin, (+)-catechin, (-)-epicatechin, (-)-epicatechin gallate and gallic acid. The highest yield amongst the flavan-3-ols was found for (-)-gallocatechin (3.7 mg/g) and (-)-epigallocatechin (1.7 mg/g). The determined content of gallic acid was 0.4 mg/g. The investigated material should be subjected for further studies to substantiate the recommendation for its wider employment in current phytotherapeutic practice. Dhaka Univ. J. Pharm. Sci. 18(2): 241-247, 2019 (December)